Influência do espaçamento, altura de corte e idade de primeiro corte na produtividade de capim santo. - Vieira, Aurilene Vasconcelos (2006)
The use of the medicinal plants is one of the oldest weapons maids for the treatment of the human illnesses and it is very already known regarding its use on the part of the popular wisdom. The sacred grass (Cymbopogon citratus (DC.) Stapf) it is a medicinal and aromatic plant, belonging to the family Poaceae. This work had as objective determines the planting spacing, the cut height and the ideal age of first cut, seeking to obtain the largest income in essential oil. For this, was settled in December of 2004, an experiment, in the area of Experimental Farm of the valley of Curu (F.E.V.C.), belonging to the Agrarian Sciences Center of the Federal University of Ceará, located in the municipal district of Pentecoste/Ce. The referred experiment was composed of the following treatments: three spacings (0,5m x 0,5m; 0,5m x 0,8m and 0,8m x 0,8m); three different times from first cut (04, 06 and 08 months) and two cut heights (15cm and 30cm of the soil), with 04 repetitions, being accomplished more two cuts in each treatment in intervals of 04 months. The used experimental delineation was in blocks at random in factorial outline 3 x 3 x 2. The obtained data were transformed for productions by hectare. As for the cut age, the best production of essential oil was obtained to the six months, the same if not verifying for the matter dries that had continuous growth. The begin of the crop to the six months after the planting in the 0,5m spacing between plants and 0,5m among rows promoted the largest production of dry matter and of the essential oil of sacred grass. About the cut height, as much the biomass production as the income of essential oil they were higher in the height of 15cm of the soil. Therefore, the C. citratus should be cultivated in the spacing 0,50m x 0,50m, picked the height of 15cm of the soil, with first harvest to the 6 months of age and consecutive cuts every four months to obtain the largest income in essential oil.